Pengelolahan Sampah Rumah Tangga Menjadi Pupuk Organik Cair Rt.05 Rw.02 Sawah Lebar Kota Bengkulu - Saleh, Gathan Raihan Al; Prastio, Yulian; Ameli, Sahira; Gusman, Eki; Pranata, Nanik Sesi; Carolina, Cynthia; Hermana, M. Arafat; Susena, Karona Cahya (Jurnal Dehasen Untuk Negeri, 2026)
The problem of household waste management remains a challenge in the Neighborhood Association (Rukun Tetangga) 05 and Community Association (Rukun Warga) 02 areas of Sawah Lebar Village, Bengkulu City. Most residents lack the awareness and skills to manage organic waste, resulting in waste being simply thrown away and causing environmental pollution. This community service activity aims to empower residents to process household waste into liquid organic fertilizer that is beneficial for plants and the environment. The implementation method is carried out in a participatory manner through stages of socialization, training in making liquid organic fertilizer, fermentation practices, mentoring, and evaluation of results. The results of the activity show an increase in community knowledge and skills in processing organic waste into useful products. Most participants have been able to produce liquid organic fertilizer independently with good results, marked by changes in color, aroma, and pH that meet the standards for natural liquid fertilizer. This program also has an impact on reducing the volume of organic waste in the environment and increasing community awareness of the importance of maintaining cleanliness and environmental sustainability. This activity has succeeded in becoming a practical solution in turning waste problems into opportunities for community empowerment.